Sztropkó – a felső-magyarországi reformáció ismeretlen fejezete - KÓNYA, Péter (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Stropkov – An Unknown Chapter of the Upper Hungarian Reformation The history of the Reformation in the Upper Zemplin town of Stropkov has remained outside the interest of history and church history. Nevertheless, Stropkov was Protestant for several decades. The establishment of the Reformation in the town was made possible by the lordship of Peter and Gábor Perényi in the second third of the 16th century. The existence of a Reformed parish is evidenced by three mentions from the late 16th and early 17th centuries. The Protestant period in the history of Stropkov ended with a change of landlords when János Pethő of Gerse became the owner of the entire estate. Baron István Pethő invited Franciscans from Poland to the town, who re-Catholicized Stropkov in a short time. The town, along with the estate, thus became the first re-Catholicized area in the Zemplin region and one of the first in the whole of Upper Hungary.